2014
DOI: 10.1152/ajpheart.00027.2014
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 deficiency exacerbates ischemia-reperfusion injury: implication for aged hearts

Abstract: Ischemia-reperfusion (IR) injury is significantly worse in aged hearts, but the underlying mechanisms are poorly understood. Age-related damage to mitochondria may be a critical feature, which manifests in an exacerbation of IR injury. Silent information regulator of transcription 3 (SIRT3), the major mitochondrial NAD(+)-dependent lysine deacetylase, regulates a variety of functions, and its inhibition may disrupt mitochondrial function to impact recovery from IR injury. In this study, the role of SIRT3 in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(150 citation statements)
references
References 58 publications
7
142
1
Order By: Relevance
“…Sirt3 ablation in the SIRT3-KO and dKO mice manifests in the development of cardiac concentric hypertrophy (Figure 2, G and H), consistent with the global SIRT3-KO literature (9, 10). We also found a role of SIRT3 for normal contractile function, which may explain the increased susceptibility to cardiac stressors in the global SIRT3-KO mouse (9)(10)(11). Given that global SIRT3-KO mice only show differences in cardiac function from WT controls upon cardiac stress (9)(10)(11), the findings that the FXN-KO and dKO mice showed no functional differences at baseline are consistent.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Sirt3 ablation in the SIRT3-KO and dKO mice manifests in the development of cardiac concentric hypertrophy (Figure 2, G and H), consistent with the global SIRT3-KO literature (9, 10). We also found a role of SIRT3 for normal contractile function, which may explain the increased susceptibility to cardiac stressors in the global SIRT3-KO mouse (9)(10)(11). Given that global SIRT3-KO mice only show differences in cardiac function from WT controls upon cardiac stress (9)(10)(11), the findings that the FXN-KO and dKO mice showed no functional differences at baseline are consistent.…”
Section: Discussionsupporting
confidence: 72%
“…We also found a role of SIRT3 for normal contractile function, which may explain the increased susceptibility to cardiac stressors in the global SIRT3-KO mouse (9)(10)(11). Given that global SIRT3-KO mice only show differences in cardiac function from WT controls upon cardiac stress (9)(10)(11), the findings that the FXN-KO and dKO mice showed no functional differences at baseline are consistent. As such, we predict that cardiac induced-stress in the FXN-KO and dKO mice might reveal an exacerbated maladaptive response to the stress in the dKO model.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Despite recent advances in redox biology and aging research (9,21,27,33,37,49,51,52,55,59,65,72,97), the role of ROS in the cerebromicrovascular effects of CR remains elusive. To assess cellular peroxide production, we used the cell-permeant oxidative fluorescent indicator dye CM-H 2DCFDA [5 (and 6)-chloromethyl-2=,7=-dichlorodihydrofluorescein diacetateacetyl ester; Invitrogen, Carlsbad, CA] as we previously reported (16,86).…”
Section: Animals and Dietmentioning
confidence: 99%
“…SIRT3 has been shown to block cardiac hypertrophy by reducing ROS synthesis from the mitochondria (Kim et al 2010). A recent study of Porter et al (2014) showed that under ischemic/reperfusion insult, at heart level, SIRT3 +/− adult and wild-type aged mice showed a similar phenotype of injury, resulting in a significant myocardial infarction area with respect to wild-type adult hearts. Moreover, the mitochondria isolated from wild-type aged heart possess a higher level of protein acetylation as observed in SIRT3 +/− hearts.…”
Section: The Sirtuin Familymentioning
confidence: 99%